2012
DOI: 10.1182/blood-2011-11-393801
|View full text |Cite
|
Sign up to set email alerts
|

Donor versus no-donor comparison of newly diagnosed myeloma patients included in the HOVON-50 multiple myeloma study

Abstract: To prospectively evaluate allogeneic stem cell transplantation (allo-SCT) for myeloma as part of first-line therapy, a donor versus no-donor analysis was performed of patients treated in the HOVON-50 study, a study that was originally designed to examine thalidomide combined with intensive therapy. Two hundred sixty patients having received an autologous-SCT fulfilled the criteria to be included, 138 patients without an HLA-identical sibling donor and 122 patients with a donor. After a median follow-up of 77 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 25 publications
5
68
4
Order By: Relevance
“…17,18,21 They are, however, worse than those for patients undergoing upfront RIC allo-SCT, which is not unexpected, given the prolonged disease history and more extensive prior therapies. [4][5][6][7][8][9][10][11][12] Although the relatively high NRM that we observed has to be taken into consideration, the data presented in this manuscript show that CMV-seronegative patients who have a CMV-seronegative donor have a substantially reduced NRM that translates into an encouraging 5-year survival of 440%. Considering that almost half (44.6%) of the patients in this study had undergone two or more prior autografts, our findings provide support to the notion that RIC allo-SCT can be an effective treatment option for some heavily pretreated patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…17,18,21 They are, however, worse than those for patients undergoing upfront RIC allo-SCT, which is not unexpected, given the prolonged disease history and more extensive prior therapies. [4][5][6][7][8][9][10][11][12] Although the relatively high NRM that we observed has to be taken into consideration, the data presented in this manuscript show that CMV-seronegative patients who have a CMV-seronegative donor have a substantially reduced NRM that translates into an encouraging 5-year survival of 440%. Considering that almost half (44.6%) of the patients in this study had undergone two or more prior autografts, our findings provide support to the notion that RIC allo-SCT can be an effective treatment option for some heavily pretreated patients.…”
Section: Discussionmentioning
confidence: 84%
“…3 Over the last decade, a number of studies investigated up-front reduced intensity-conditioned (RIC) allo-SCT and reported substantially lower NRM rates compared with MA allo-SCT. [4][5][6][7][8][9][10][11][12][13] Whereas some of these studies reported better longterm outcomes with RIC allo-SCT compared with tandem autologous hematopoietic SCT (auto-SCT), others failed to demonstrate a benefit of up-front RIC allo-SCT. Therefore, there is widespread reluctance to offer patients' up-front allo-SCT, which is at least partly due to prolonged remissions that can be achieved following induction and/or maintenance therapy with novel agents.…”
Section: Introductionmentioning
confidence: 96%
“…1,2 These data led to several prospective randomized studies comparing tandem autoallo transplant to single or tandem auto-PSCT. [3][4][5][6][7][8][9][10] Overall, studies show a lower relapse rate in allograft-containing arms but with no OS benefit. Two of the studies with long-term follow-up show improved PFS and OS in favor of tandem auto-allograft.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 In 2007, Bruno et al 31 described the outcomes of 245 patients, o 65 years old, biologically assigned (on sibling donor availability) to allo-SCT vs a second tandem ASCT after initial induction. 31 Eighty patients with an HLA-identical sibling were assigned to 200 cGy (Gray) TBI-based allotransplant, whereas 82 patients without an HLA-identical sibling were assigned to receive a second ASCT.…”
Section: Non-myeloablative/reduced-intensity Conditioningmentioning
confidence: 99%